North American Study for the Treatment of Recurrent Epistaxis with Doxycycline: The NOSTRIL trial. (17th February 2022) - McWilliams, Justin P.; Majumdar, Shamaita; Kim, Grace H.; Lee, Jihey; Seals, Kevin; Tangchaiburana, Samantha; Gilbert, Stephanie; Duckwiler, Gary R.
Abstract: Background: Hereditary hemorrhagic telangiectasia (HHT) is a vascular bleeding disorder characterized by mucocutaneous telangiectasias and visceral arteriovenous malformations. A frequently debilitating symptom is spontaneous recurrent epistaxis. Objective: To evaluate whether doxycycline therapy improves epistaxis in HHT by using a prospective, randomized, placebo‐controlled crossover study design. Patients/Methods: Twenty‐two eligible patients between December 2017 and July 2020 at a single center were randomized to one of two study arms: doxycycline treatment followed by placebo, or vice versa. Primary outcomes measured differences in epistaxis severity between treatments. Changes in quality of life, laboratory markers of bleeding, and number of monthly blood transfusions or iron infusions were assessed as secondary endpoints. Additional post hoc endpoints included frequency and duration of dripping epistaxis and gushing epistaxis. A post hoc longitudinal analysis assessed effects of doxycycline over time. Results/Conclusions: Doxycycline was safe and well tolerated. However, there was no reduction in the three primary outcome measures, nosebleed frequency ( p  = .16), nosebleed duration ( p  = .05), and Epistaxis Severity Score ( p  = .19). Quality of life, hemoglobin level, and number of blood transfusions and iron infusions did not differ between groups. Post hoc analysis demonstrated reduction in instances of gushing ( p  = .02) with doxycycline, although this finding is of unclear clinical significance. Post hoc longitudinal analysis showed reduction in frequency (mean estimate of coefficient = −0.19, standard error = 0.07, p  = .01) and duration (mean estimate of coefficient = −2.33, standard error = 1.08, p  = .03) of epistaxis over time. Post hoc findings suggest possible benefit of doxycycline but should be interpreted with caution given the overall negative study. Further investigation is needed with a larger sample size and a longer treatment duration.